1979
DOI: 10.1111/j.1399-6576.1979.tb01430.x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative and Postoperative Use of Clonidine with Neurolept Anaesthesia

Abstract: The abrupt cessation of clonidine therapy can induce a withdrawal syndrome. This may also appear immediately after anaesthesia if clonidine medication is discontinued during the operation day. We studied (1) whether the withdrawal syndrome occurs postoperatively as often as otherwise when clonidine therapy is discontinued, and (2) the action of this clonidine withdrawal on the circulation as compared to patients who received clonidine without interruption during the operation day. During the recovery period in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…(%midine is a short-acting drug: three doses daily are usually required to maintain its antihypertensive action. Because the abrupt cessation of clonidine medication can induce a withdrawal syndrome (HUNYOR et al 1973, GOLDBERG et al 1977, it has been recommended that clonidine should continue to be administered on the operation day (BRODSKY & BRAVO 1976, KAUKINEN et al 1979. Therefore, it is a common practice to anaesthetize patients who are receiving clonidine medication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(%midine is a short-acting drug: three doses daily are usually required to maintain its antihypertensive action. Because the abrupt cessation of clonidine medication can induce a withdrawal syndrome (HUNYOR et al 1973, GOLDBERG et al 1977, it has been recommended that clonidine should continue to be administered on the operation day (BRODSKY & BRAVO 1976, KAUKINEN et al 1979. Therefore, it is a common practice to anaesthetize patients who are receiving clonidine medication.…”
Section: Discussionmentioning
confidence: 99%
“…The abrupt cessation of clonidine therapy can induce a withdrawal syndrome which consists of a hypertensive crisis and other symptoms of sympathetic overstimulation (HUNYOR et al , GOLDBERC et al 1977. Clonidine therapy must thus be continued throughout the day of operation in order to avoid the possible withdrawal syndrome (BRODSKY & BRAVO 1976, KAUKINEN et al 1979). Because of its sedative effect it could be expected that clonidine also potentiates the action of anaesthetics.…”
mentioning
confidence: 99%
“…In the field of anesthesiology, reports on the relationship between clonidine and anesthesia appeared in the late 1970s. In 1978, Kaukinen et al 21 reported that the use of clonidine as premedication for neuroleptanalgesia suppressed the elevation of blood pressure during anesthesia. In recent years, with the development of the more selective a 2 -agonists, experimental and clinical studies have been conducted chiefly on the analgesic, sedative, and anesthetic effects of a 2 -agonists.…”
Section: Discussionmentioning
confidence: 98%
“…In recent years, with the development of the more selective a 2 -agonists, experimental and clinical studies have been conducted chiefly on the analgesic, sedative, and anesthetic effects of a 2 -agonists. 20,21 The actions of clonidine on the cardiovascular system include a centrally exerted antihypertensive action, resulting in bradycardia through the activation of presynaptic a 2 -receptors at the peripheral cardiac sympathetic nerve endings, 22 and an action on the coronary arteries that increases the coronary blood flow by releasing an endothelium-derived relaxing factor (nitric oxide). 14 The antihypertensive and coronary blood flow-increasing actions are considered to be favorable in patients with hypertension or ischemic heart disease, but excessive bradycardia and hypotension are not desirable.…”
Section: Discussionmentioning
confidence: 99%
“…The alpha 2-adenoceptor agonist have been used as premedicants because of their beneficial properties in anesthesia. Clonidine, which is mainly used as an antihypertensive agent, has many properties of an ideal premedicant, and it also has beneficial effect on the hemodynamics during stressful conditions like laryngoscopy and endotracheal intubation [15] . The effect of clonidine on the hemodynamic variable are dose related, but increase in dose to more than 4 micrograms/kg do not further enhance the efficacy.…”
Section: Discussionmentioning
confidence: 99%